2016
DOI: 10.1016/j.neuron.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Hippocampal Sharp-Wave-Ripple Events and Vicarious Trial and Error Behaviors in Decision Making

Abstract: Summary Current theories posit that memories encoded during experiences are subsequently consolidated into longer-term storage. Hippocampal sharp-wave ripple (SWR) events have been linked to this consolidation process during sleep, but SWRs also occur during awake immobility, where their role remains unclear. We report that awake SWR rates at the reward site are inversely related to the prevalence of vicarious trial and error (VTE) behaviors, thought to be involved in deliberation processes. SWR rates were dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 57 publications
8
126
0
Order By: Relevance
“…Under similar conditions in rodents replay is known to occur preferentially during brief high-frequency sharp-wave ripple (SWR) events in the hippocampus (19)(20)(21). In contrast, slower theta-related sequence events are observed during active navigation and decision making in rodents (19,20,22,23). Thus, during memory retrieval, we expected that performance in the current experiment would be supported by replay events with a relatively longer lag between states.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Under similar conditions in rodents replay is known to occur preferentially during brief high-frequency sharp-wave ripple (SWR) events in the hippocampus (19)(20)(21). In contrast, slower theta-related sequence events are observed during active navigation and decision making in rodents (19,20,22,23). Thus, during memory retrieval, we expected that performance in the current experiment would be supported by replay events with a relatively longer lag between states.…”
Section: Introductionmentioning
confidence: 89%
“…Previous research demonstrating replay, which did not link replay to behavior, identified an approximately 40-50 ms lag between states (elements of a sequence) either during tasks involving lengthy planning periods or during rest periods (17,18). Under similar conditions in rodents replay is known to occur preferentially during brief high-frequency sharp-wave ripple (SWR) events in the hippocampus (19)(20)(21). In contrast, slower theta-related sequence events are observed during active navigation and decision making in rodents (19,20,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, iterative viewing could serve to increase processing and binding of interrelationships among stimuli. Rodents exhibit similar iterative viewing behaviors, which are strongly linked to memory formation [41], are disrupted by hippocampal lesions [56, 57], and are associated with hippocampal theta activity and sharp-wave ripples [58, 59]. Other self-generated exploratory behaviors that enhance learning in the rodent (i.e., rearing) have been independently associated with increased hippocampal activity [60].…”
Section: Hippocampal Contributions To Exploratory Viewing For Memorymentioning
confidence: 99%
“…In a range of behavioral paradigms requiring the hippocampus, substantial time is spent outside locomotion. For example, in navigational paradigms, animals routinely pause or reduce locomotion, whether over the course of spontaneous exploratory excursions, upon attainment of the goal location, or as a consequence of imposed delays that render tasks hippocampus‐dependent (Ainge et al, ; Eilam & Golani, ; Papale, Zielinski, Frank, Jadhav, & Redish, ; Redish, ; Tolman, ; Wallace & Whishaw, ). In our own experiments using a simple navigational maze, we find that unambiguous still state periods comprise ∼25% of all time in the task (Kay et al, ).…”
Section: Three Brain States In the Hippocampusmentioning
confidence: 99%